Healthcare Systems and Health Informatics : Using Internet of Things. - Mehra, Pawan Singh; Goyal, Lalit Mohan; Dagur, Arvind; Dwivedi, Anshu Kumar ([Place of publication not identified] : CRC Press, 2022)
This book covers the fundamentals of IoT and healthcare systems for carrying out system architectures, protocols, wearable devices, and interoperability. It explores major challenges in AI and smart computing in resource-constrained IoT-based applications along with cost, energy efficiency, and the availability of quality service. Healthcare Systems and Health Informatics: Using the Internet of Things explores the role of Artificial Intelligence and Smart Computing in health informatics and healthcare with an emphasis on clinical data management and analysis for precise prediction and prompt action. It presents cutting-edge tracking, monitoring, real-time assistance, and security for IoT in healthcare and discusses broadly wearable sensors and IoT devices and their role in smart living assistance. The book goes onto describing a system model and architecture for a clear picture of energy conservation-based IoT in healthcare and explains the challenges and opportunities with IoT-based healthcare industries. A study of the threats and impacts along with the need for information security is also included. Chapters written by experts in the field, this book provides a comprehensive description of the important aspects of IoT and Health from a beginner to advance level perspective and is ideal for researchers, academicians, students, persons in industry, technologists, and entrepreneurs.
Unit 1: Introduction to IoT Based Healthcare Devices. 1. Internet of Things: The Need, Energy Conservations, and Benefits. 2. Wireless Sensor Network and Internet of Things: Synergy and Barriers. 3. Wearable Devices and IoT: Applications and Constraints. 4. Energy Conservation in IoT-Based Smart Hospital Management Systems. 5. System Architecture for IoT Devices and their Applications in Healthcare. Unit 2: Energy Conservation Based IoT Systems for Healthcare Sector: AI and Smart Computing. 6. Artificial Intelligence and Smart Computing in IoT Based Healthcare: An Overview. 7. Data Analytics and Mining in IoT Based Healthcare Support System. 8. Edge/ Fog Computing in IoT Based Healthcare Support System. 9. Machine Learning and Deep Learning in IoT Based Healthcare Support system. Unit 3: Energy Conservation Based IoT Systems for Healthcare Industries: Opportunities and Challenges. 10. 6G Networks, Internet of Things and Healthcare: Prospective and Potential. 11. Uninterrupted Health Monitoring Using IoT Based Wearable Devices. 12. Smart Hospitals and Pathological Labs with IoT Devices. 13. Transparent Insurance Claims Made Easy Using IoT Based Healthcare Devices. 14. IoT Based Mobile Healthcare System. Unit 4: Security and Privacy in Energy Conservation Based IoT Healthcare. 15.Threats and its Impact on IoT Based Healthcare. 16. Necessity of Information Security and Privacy in IoT Based Healthcare. 17. Information Security: Patient Awareness and Healthcare Responsibility. 18. Protecting Digital Information of Patients in IoT Based Healthcare.
OCLC-licensed vendor bibliographic record.
Keywords: Medical care -- Computer network resources; Internet of things; TECHNOLOGY / Manufacturing